2021
DOI: 10.3390/genes12010103
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Peripartum Cardiomyopathy: Current Knowledge, Future Directions and Clinical Implications

Abstract: Peripartum cardiomyopathy (PPCM) is a condition in which heart failure and systolic dysfunction occur late in pregnancy or within months following delivery. Over the last decade, genetic advances in heritable cardiomyopathy have provided new insights into the role of genetics in PPCM. In this review, we summarise current knowledge of the genetics of PPCM and potential avenues for further research, including the role of molecular chaperone mutations in PPCM. Evidence supporting a genetic basis for PPCM has eman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…Goli et al (2021) identified 70 mutations in 12 genes from PPCM sampling. Another recent study found 21 genes were associated with cardiomyocytes that contribute to the genetic predisposition of PPCM patients (Spracklen et al 2021). Some of these gene mutations were also reported by Ware et al (2016) who constructed sequencing libraries of 43 genes and identified 26 truncating variants in 8 genes that were associated with dilated cardiomyopathy.…”
Section: Cardiomyocyte Gene Mutations That Contribute To Ppcmmentioning
confidence: 78%
“…Goli et al (2021) identified 70 mutations in 12 genes from PPCM sampling. Another recent study found 21 genes were associated with cardiomyocytes that contribute to the genetic predisposition of PPCM patients (Spracklen et al 2021). Some of these gene mutations were also reported by Ware et al (2016) who constructed sequencing libraries of 43 genes and identified 26 truncating variants in 8 genes that were associated with dilated cardiomyopathy.…”
Section: Cardiomyocyte Gene Mutations That Contribute To Ppcmmentioning
confidence: 78%
“…However, peripartum cardiomyopathy has been reported as a part of familial DCM, 89 and aggregating evidence has demonstrated the strong genetic basis of familial peripartum cardiomyopathy. 90 , 91 Factually, in roughly 20% of patients with peripartum DCM, screening for cardiomyopathy‐causative genes reveals pathogenic mutations, with TTN truncations most commonly implicated, occurring in approximately 10% of patients with peripartum DCM. 91 , 92 Hence, it is the right time to offer genetic testing to patients with peripartum DCM, 93 and referral for genetic testing should be considered if there is a positive family history of cardiomyopathy or sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…Peripartum cardiomyopathy (PPCM) is defined as HFrEF (LVEF <45%) occurring within the last month before or 6 months after delivery in women without previous heart disease. 36,37 [37][38][39] Therefore, genetic testing is recommended in patients with PPCM, particularly in cases of familial history of cardiomyopathy. 1,37 Patients often display severe HF and a markedly reduced LVEF <35% with right ventricular (RV) involvement.…”
Section: Peripartum Cardiomyopathymentioning
confidence: 99%